Hydrothermal synthesis and characterization of the eulytite phase of bismuth germanium oxide powders. Issue 10 (16th May 2014) - Boyle, Timothy J.; Sivonxay, Eric; Yang, Pin; Rodriguez, Mark A.; Hernandez-Sanchez, Bernadette A.; Bell, Nelson S.; Velazquez, Andrew; Kaehr, Bryan; Bencomo, Marlene; Griego, James J.M.; Doty, Patrick
Abstract: Abstract : A simple hydrothermal route to the eulytite phase of bismuth germanium oxide (E-BGO: Bi4 (GeO4 )3 ) that required no post-processing has been developed. The E-BGO material was isolated from a mixture of bismuth nitrate pentahydrate and a slight excess of germanium oxide in water under hydrothermal conditions (185 °C for 24 h). The resultant materials were characterized by powder x-ray diffraction, scanning electron microscopy, transmission electron microscopy, and luminescence measurements to verify the particle's phase (eulytite), morphology, size, and response to a variety of excitation energy sources, respectively. Photoluminescence spectroscopic response from E-BGO pellets indicated that the samples exhibited a strong emission peak consistent with an x-ray induced luminescence of a E-BGO single crystal (500 nm excited at 285 nm). Cathodoluminescent properties of the E-BGO displayed a broadband spectrum with a maximum at 487 nm. The growth process was consistent with a standard Oswald ripening and LaMer growth processes.